Exploring CGIAR Level Agricultural Results Interoperable System Architecture (CLARISA) - Tobon, Hector; Col, Valentina de; Ramírez, Margarita M.; Bonaiuti, Enrico; Abreu, David (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2022)
CLARISA (https://clarisa.cgiar.org/) is the CGIAR Level Agricultural Results Interoperable System Architecture, a web service that helps collect and transform raw data of CGIAR research and activities into standardised and aggregated information. CLARISA is pivotal in supporting interoperability by enabling Management Information Systems (MISes) such as MARLO (Managing Agricultural Research for Learning and Outcomes), MEL (Monitoring, Evaluation and Learning), and Centre specific systems (e.g., CIAT-MARLO) to communicate with each other in the language needed for the CGIAR system-level reporting. This allows CGIAR to communicate with external partners in a clear, accountable, and transparent way. CLARISA represents an essential step of business intelligence towards enabling more effective strategic and operational decision-making. It is equipped with features to inform plans of work and budget and to appraise research progress and global goals for development. Additional enhancements and integration between program and knowledge management aspects could lead to enhanced quality and completeness of monitoring and reporting processes and harmonization of reporting standards at the CGIAR system level.